PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran IPA Kelas V SD Negeri 20 Pagar Alam) - Abu Bakar (DIADIK, 2020)
The purpose of this study (1) The application of the scientific approach to increase the indepedence of studens in science subjects fifth grade 20 Pagar Alam. (2) The application of scientific approach in improving learning achievement of students in science  subjects fifth grade 20 Pagar Alam. (3) The effectiveness of the application of the scientific approach when compared with conventional learning methods. The population in this study is the fifth grade students of SDN 20 Pagar Alam totaling 58 people. For sampling done by total sampling that the sample is determined by making the entire population being sampled, the sample which act as a class action is the students’ class VC totaling 18 students, the study sample for a class experiment is student-class VA toaling 20 students. To control class is the class VB totaling 20 students. Data collection techniques using observation sheets, and test. Results of this research is to study the application of this scientific approach can improve the independence of  students in lerning, especially in science subjects